Blaski i cienie „Deklaracji praw człowieka i obywatela" z 1789 r. - Drozdowicz, Zbigniew (Wydawnictwo Fundacji Humaniora, 2017)
In these remarks I do recall again the very “Declaration of rights of the Man and of the Citizen,” which was for some and still is a testimony of reaching the most moderate part of the French society such a philosophical and political wisdom that was lacking in the former generations. For others it was and still is a testimony of undermining these authentic values and greatness that was reached by those generation with such a hard effort. The evaluation of that Declaration is related of course not only to what had been written in its particular articles, but to who does it measure and what scale does he uses. In these remarks I recall just two of such scales, ie. the one used by liberals and the one used by the traditionalists (called today conservatives). Recalling also other philosophical and political options would certainly widen both, the list of ups and downs of that enlightenment thinking on man and citiz.
Keywords: declaration of human and citizen rights; pros and cons; philosophical and political controversies